MEDIA VIDEO ANIMASI MINDFUL EATING DAPAT DIGUNAKAN UNTUK MEMBANTU MENGATASI DISORDERED EATING PADA MAHASISWA - Ramadhani, Aisyah Intan; Andayani, Tri Rejeki; Hikmayani, Nur Hafidha (Media Penelitian dan Pengembangan Kesehatan, 2024)
Disordered Eating (DE) or eating behavior problems are one of the issues that are increasingly significant among college students. Academic pressures and cultural changes influence the concept of the ideal body, leading to unhealthy eating behaviors. Mindful Eating (ME), which emphasizes awareness and appreciation of eating behaviors, effectively addresses disordered eating behaviors. However, there are still many cases of DE among collage students, especially women. This research aimed to develop a canvas-based animation video to help college students overcome DE. The type research method in this study used Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model, but only up to the development stage in this study. Canva-based animation video validation involves three experts: expert materials, linguists, and media experts, with an average result of 80.3 (decent category, revised as necessary).  Next, it was tested on prospective users (n = 37) who were selected by simple random sampling. The results of product assessment by prospective users amounted to 91.1 (very feasible category, no need to revise). The ME Knowledge Questionnaire measured the impact of video use (reliability = 0.621). The results of the comprehension score based on the pre-test and post-test on students obtained an average N-Gain score of 0.84 with an average score of 0.84 with a high category. Based on the analysis results, it can be concluded that ME video products are feasible to use as learning media to increase ME knowledge and overcome ED problems in collage students.